2020
DOI: 10.3390/toxins12100635
|View full text |Cite
|
Sign up to set email alerts
|

The Toxin-Antitoxin Systems of the Opportunistic Pathogen Stenotrophomonas maltophilia of Environmental and Clinical Origin

Abstract: Stenotrophomonas maltophilia is a ubiquitous environmental bacterium that has recently emerged as a multidrug-resistant opportunistic pathogen causing bloodstream, respiratory, and urinary tract infections. The connection between the commensal environmental S. maltophilia and the opportunistic pathogen strains is still under investigation. Bacterial toxin–antitoxin (TA) systems have been previously associated with pathogenic traits, such as biofilm formation and resistance to antibiotics, which are important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…A. baumannii clinical isolate II-a [ 31 ] and S. maltophilia clinical isolate SM3 [ 32 ] were chosen for the aPDT approach study. In all experiments, A. baumannii was grown in Luria-Bertani (LB) and S. maltophilia was grown in Tryptone soya broth (TSB) medium; both isolates were grown at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A. baumannii clinical isolate II-a [ 31 ] and S. maltophilia clinical isolate SM3 [ 32 ] were chosen for the aPDT approach study. In all experiments, A. baumannii was grown in Luria-Bertani (LB) and S. maltophilia was grown in Tryptone soya broth (TSB) medium; both isolates were grown at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Six Stenotrophomonas maltophilia and eight Chryseobacterium spp. antibiotic-resistant isolates were used for genomic library construction; all bacteria were isolated from farming field soil in Lithuania during the year 2016 [ 17 , 65 ]. The isolates were designated as resistant if the MIC of antibiotic value matched EUCAST clinical breakpoints (v. 7.0, 2017, PK/PD (non-species related).…”
Section: Methodsmentioning
confidence: 99%
“…Bleriot et al studied the molecular mechanisms associated with chlorhexidine (CHLX) adaptation in two clinical strains of Klebsiella pneumoniae by phenotypic and transcriptomic analyses and their association with a new PemK/PemI TA system [12]. Klimkaitè et al have found by bioinformatic analysis 49 putative TA systems in Stenotrophomonas maltophilia, and asked whether clinical and environmental isolates contain a different set of type II TA systems [13]. The authors observed that RelBE, HicAB, and the previously undescribed COG3832-ArsR operon were present solely in clinical S. maltophilia isolates collected in Lithuania, while HipBA was more frequent in the environmental ones.…”
mentioning
confidence: 99%